2016
DOI: 10.1039/c6cp05394g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation of dihydronicotinamide adenine dinucleotide (NADH): comparison of highly oriented pyrolytic graphite (HOPG) and polycrystalline boron-doped diamond (pBDD) electrodes

Abstract: (2016) Electrochemical oxidation of dihydronicotinamide adenine dinucleotide (NADH) : Comparison of highly oriented pyrolytic graphite (HOPG) and polycrystalline boron-doped diamond (pBDD) electrodes. Physical Chemistry Chemical Physics. Permanent WRAP URL:http://wrap.warwick.ac.uk/81637 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
(110 reference statements)
2
13
0
Order By: Relevance
“…Macroscopic measurements at O-pBDD revealed that while it is less active than HOPG, it is also less susceptible (but not immune) to surface fouling, while microscopic voltammetric measurements (with SECCM) revealed a strong grain dependence, with activity scaling with local (grain-dependent) dopant density. 212 Local electrochemical measurements with SECCM can be coupled with co-located ex situ electron back scatter diffraction (EBSD) characterization to resolve structure-activity at the individual grains and GBs that comprise a polycrystalline surface. 184,213 This "pseudo single-crystal approach" was employed to understand the microscopic factors (surface termination and doping level) determining the electrochemical solvent window (i.e., the potential range over which the solvent/electrolyte is stable to electrolysis) of O-pBDD and hydrogen-terminated polycrystalline BDD (H-pBDD) in aqueous potassium chloride.…”
Section: Carbon Materialsmentioning
confidence: 99%
“…Macroscopic measurements at O-pBDD revealed that while it is less active than HOPG, it is also less susceptible (but not immune) to surface fouling, while microscopic voltammetric measurements (with SECCM) revealed a strong grain dependence, with activity scaling with local (grain-dependent) dopant density. 212 Local electrochemical measurements with SECCM can be coupled with co-located ex situ electron back scatter diffraction (EBSD) characterization to resolve structure-activity at the individual grains and GBs that comprise a polycrystalline surface. 184,213 This "pseudo single-crystal approach" was employed to understand the microscopic factors (surface termination and doping level) determining the electrochemical solvent window (i.e., the potential range over which the solvent/electrolyte is stable to electrolysis) of O-pBDD and hydrogen-terminated polycrystalline BDD (H-pBDD) in aqueous potassium chloride.…”
Section: Carbon Materialsmentioning
confidence: 99%
“…SECCM is also a useful tool to investigate local electrochemical reactions of graphite , and graphene. , In particular, the influence of the edge states of graphite/graphene in electrochemistry is a hot topic because of their unusual density of states phenomena. Unwin and co-workers first observed that the basal plane of pristine graphite in any grade of highly oriented pyrolytic graphite (HOPG) sample shows electron transfer activities .…”
Section: Scanning Electrochemical Cell Microscopymentioning
confidence: 99%
“…Furthermore, SECCM imaging showed that the basal plane supports faster electron transfer, which is not clearly observed at the step edges. Once HOPG is cleaved and exposed to air, its surface conductivity and electrochemical response deteriorate, which is strongly associated with the electrochemical activity on the top layer. Thus, for immaculate exfoliated graphene surfaces, samples should be carefully prepared by controlling the atmosphere, considering oxidation or surface contamination by the atmosphere Figure b shows an SECCM image of the surface of graphene with various numbers of step edges (layers).…”
Section: Scanning Electrochemical Cell Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of NADH at conventional electrodes, namely glassy carbon, Pt, and Au, requires particularly high overpotentials and induces massive passivation of the surface [4,5,6,7]. For this reason, many materials have been developed and studied so far, aiming at realization of efficient amperometric sensors for the detection of this analyte [8,9,10].…”
Section: Introductionmentioning
confidence: 99%